Carrier recovery for digital modulation binary phase shift keying (costas loop) / Mohamad Azuri Mohamad Sharif - Mohamad Sharif, Mohamad Azuri (2014)
This project consists of studies about digital signals on how the signal is being transmitted and received, is to construct a carrier recovery circuit using MATLAB for the most common BPSK receiver, including testing and implementation of the circuit .Observing the output signals of various data signals. Keywords - BPSK signal, Carrier recovery, Costas Loop.